Proučevanje zgodovine političnih idej - Pikalo, Jernej (Javnost (Ljubljana), 2010)
The article examines the development of research methods in the history of political ideas from canonist approach through the Cambridge School to poststructuralist methodologies. The Cambridge School is predominantly focused on author and its intentions, and less on reader or interpreter of political ideas. The article calls for dialogical approach to interpretation of political ideas. The issue of discursive formations and non-textual factors in determining of meanings in the history of political ideas is emphasised. The article reveals genealogies, points of agreements and disagreements of the Cambridge School and other methodological approaches situated in a wider, including Slovenian, context of social and political theories.
Keywords: politična zgodovina; politične teorije; metodologija